Інноваційно-активні підприємства: сутність та фактори впливу на їх розвиток - Андрюшко, А. К.; Andryushko, А. (КНТУ, 2013)
У статті визначено сутність поняття інноваційно-активні підприємства, узагальнено підходи до їх оцінки, а також виявлено зовнішні фактори впливу на їх розвиток. Встановлено, що інноваційну активність доцільно розглядати як комплексний процес, спрямований на створення, виробництво та удосконалення нових видів продукції, послуг, технологій, організаційних форм, поява яких на ринку може дати додатковий дохід. The aim of the paper is to define the essence of the concept of innovatively active enterprises, to generalize approaches to their assessment and identify external influences on their development. The paper states that scientists define an innovatively active enterprise as those, which are engaged in innovative activities. Innovative activities traditionally include: implementation of research and development, obtaining machinery, equipment, facilities; acquisition of new technologies and other fixed assets, also capital costs connected with the introduction of innovations; industrial design, and other types of preparation for the production of new products, introduction of new methods of production, implementation of marketing innovation and so on. All external factors, which influence the emergency of an enterprise innovative activity, can be divided into international, national and market. Thus, innovative activity should be considered as a complex process aimed at the creation, production and improvement of new products, services, technologies, organizational forms. Their appearance at the market can provide extra income.
Innovatively active enterprises: nature and impact factors of their development
Keywords: інновації; інноваційно-активні підприємства; зовнішнє середовище; фактори; innovation; innovatively active enterprises; environment factors